Pengaruh Aplikasi Biourin Gajah terhadap Pertumbuhan dan Hasil Tanaman Sawi Hijau (Brassica juncea L.) - BENITA NATHANIA; I MADE SUKEWIJAYA; NI WAYAN SRI SUTARI (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2012)
ABSTRACT Application Effect of Elephant Bio-Urine on Green Mustard Plant Growth and Yield The experiment conducted in greenhouse located in experimental garden of Agriculture Faculty Udayana University. The experiment aims to find the effect of elephant’s bio-urine application on plant growth and yield of mustard greens (Brassica juncea L.). The experiment uses a completely randomized design (CRD) with one treatment factor and ten replications. The treatment is elephant’s Bio-urine concentration which is consists of six levels: 0 ml / l (B0), 100 ml / l (B1), 200 ml / l (B2), 300 ml / l (B3), 400 ml / l (B4), and 500 ml / l (B5). The results showed that treatment of elephant’s bio-urine concentration gives a significant effect on all variables were observed. Elephant’s bio-urine concentrations 300 ml/l gave the best growth and highest yield of total dry weight, 3.55 g/plant and total fresh weight 42.85 g/plant. Meanwhile, elephant’s bio-urine concentrations 500 ml/l gave poor growth and lowest yield of total dry weight, 2.20 g/plant and also the lowest total fresh weight 24.22 g/plant. Key words: elephant bio-urine, green mustard